Potential impact of antiarrhythmic drugs versus implantable defibrillators on the management of ventricular arrhythmias: the Midlands trial of empirical amiodarone versus electrophysiologically guided intervention and cardioverter implant registry data. Issue 1 (1st July 1998) - Pathmanathan, R K; Lau, E W; Cooper, J; Newton, L; Skehan, J D; Garratt, C J; Griffith, M J
Abstract : Background: Survival was prolonged in selected patients with sustained ventricular arrhythmias who received implantable cardioverter defibrillators (ICDs) in the antiarrhythmics versus implantable defibrillators (AVID) study. The Midlands trial of empirical amiodarone versus electrophysiologically guided intervention and cardioverter implant in ventricular arrhythmias (MAVERIC) registry is a population based trial. Objective: To determine the number of patients who satisfy the AVID criteria because of the high cost of ICDs. Design: Observational study, based on a continuing trial. Setting: All coronary care units in the Midlands region in the United Kingdom (population 9.1 million). Patients: Patients presenting to a coronary care unit with sustained ventricular arrhythmias not related to an acute myocardial infarction are entered onto the registry. Those who consent to the MAVERIC study are randomised to receive either empirical amiodarone or electrophysiologically guided treatment. Demographic data, details of clinical presentation, and echocardiographic findings are collected. These data have been used to calculate the number of patients who satisfy the AVID criteria and would benefit from ICD implantation. The financial implications have been calculated for the region and nationally. Results: 132 patients were entered onto the registry during the first five months of the MAVERIC study; 69 patients fulfilled the AVID criteria. Extrapolation of these data over a 12 month period suggests implantation of at least 166 new ICDs (compared with 23 implants in 1996). This would increase the UK ICD implant rate from five to at least 18 per million of the population, costing the National Health Service £24.1 million per annum. Conclusion: Application of the AVID criteria in the UK will cause a great increase in the ICD implant rate, with serious financial implications.